(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
The songbird brain has a system of interconnected nuclei that are specialized for singing and song learning. Electrophysiological findings indicate a role for the glutamatergic neurons in the song system. Vesicular glutamate transporter 2 (vGluT2) is considered to be a specific biomarker of glutamatergic neurons in birds. Neurons receiving glutamatergic afferents express mRNA of ionotropic glutamate receptor subunits. This study examined expression of vGluT2 and glutamate receptor subunit mRNAs in nuclei of the song pathways of male zebra finch brain by in situ hybridization. VGluT2 mRNA was revealed high density of expression in the song nuclei, namely HVC, lateral magnocellular nucleus of the anterior nidopallium, and robust nucleus of the arcopallium. Area X did not show expression of vGluT2 mRNA. Nuclei in the descending motor pathway (dorsomedial nucleus of the intercollicular complex and retroambigual nucleus) were expressed vGluT2 mRNA. Target nuclei of vGluT2 mRNA-expressing nuclei showed hybridization signals for mRNAs of ionotropic glutamate receptor subunits. At least one of five subunit mRNAs (GluA1, GluA4, GluK1, GluN1, GluN2A) was expressed in song nuclei. The present findings support the existence of glutamatergic circuits in the song system in songbirds. DOI: http://dx.doi.org/10.3329/ralf.v1i1.22356 Res. Agric., Livest. Fish.1(1): 61-70, Dec 2014